Efficacy of tenapanor in managing hyperphosphatemia and constipation in hemodialysis patients: A randomized controlled trial - Naoki Suzuki; Yuuki Takeda; Akie Kabuto; Takao Konishi; Takahiro Konishi; Fumi Sumino; Hayanari Iwata; Mone Iwagami; Yusuke Kouchi; Yasumasa Hitomi; Toru Takatani; Masato Nishimura; et al. (PLoS ONE, 2025)
Introduction Tenapanor is a minimally absorbed, small-molecule inhibitor of sodium/hydrogen exchanger 3 and thus suppresses sodium absorption in the gastrointestinal tract. It is approved by the FDA for the treatment of hyperphosphatemia in dialysis patients. This randomized controlled trial evaluated its efficacy in the treatment of hyperphosphatemia and constipation in hemodialysis patients. Methods Ninety hemodialysis patients were randomized 1:1 to receive either tenapanor or standard care. Randomization was performed using a computer-generated sequence stratified by baseline serum phosphorus levels. The tenapanor group began treatment with a dosage of 10 mg/day, which was adjusted based on serum phosphorus levels. Primary outcomes were changes in serum phosphorus levels in the tenapanor and control groups and changes in stool consistency, assessed weekly using the Bristol Stool Form Scale (BSFS) in the tenapanor group. Secondary outcomes included laxative use and phosphate binder prescription patterns. Serum phosphorus levels, serum calcium, albumin, and related biochemical parameters were monitored every two weeks. Data were analyzed using intention-to-treat principles. This study was not blinded. Results Of the 90 randomized participants, 69 completed the 23-week study. Tenapanor significantly improved stool consistency and resolved constipation (BSFS types 1–2) by week 5. A transient increase in loose stools (BSFS types 6–7) occurred early, with 10 participants discontinuing due to diarrhea. Laxative use decreased significantly in the tenapanor group, from 58.2% at baseline to 35.6% at week 23 (p < 0.01). Serum phosphorus levels were decreased in both groups, with comparable control. Lanthanum carbonate prescriptions decreased significantly in the tenapanor group and were largely replaced by low-dose tenapanor. Conclusion Tenapanor improves stool consistency, reduces laxative use, and provides effective phosphorus control in hemodialysis patients and represents a promising alternative to conventional phosphate binders.